2009
DOI: 10.1007/s00402-009-0911-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after joint reconstruction or medial resection arthroplasty for anterior SCJ instability

Abstract: We concluded that patient selection and a specific clinical indication for operative treatment are crucial. Resection of the medial clavicle results in good functional outcome when the costoclavicular ligament is preserved or reconstructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 33 publications
0
58
1
5
Order By: Relevance
“…17,20 Clavicle shortening in subjects with complex comminuted fractures (type 2B2) is a concern with TEN fixation because of potential overlapping of the fracture sites. The TEN is a flexible nail lacking arm leverage sufficient to resist the bending forces produced at a comminuted fracture site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17,20 Clavicle shortening in subjects with complex comminuted fractures (type 2B2) is a concern with TEN fixation because of potential overlapping of the fracture sites. The TEN is a flexible nail lacking arm leverage sufficient to resist the bending forces produced at a comminuted fracture site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Again, all 8 patients were completely satisfied with the result at a mean follow-up of 31 months. In patients with anterior instability, Panzica et al 3 also reported good to excellent outcomes in 6 patients treated with open resection arthroplasty with a mean follow-up of 9.9 years.…”
Section: Discussionmentioning
confidence: 97%
“…Open reduction should be considered when closed reduction and nonoperative treatment have failed. Indications for open reduction are recurrent posterior luxations and anterior luxations with pain, discomfort, and persistent instability [12,13,15,17]. Habitual luxations, caused by general hyperlaxity, should be distinguished from luxations caused by previous trauma and should be treated nonoperatively [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous treatment options described in the literature [1-4, 7, 9, 10, 12, 13, 17, 18, 23], but studies reporting the results of different techniques are few and mostly outdated [1,3,4,9,12,17]. Therefore, there is no favorable surgical treatment for sternoclavicular luxations when nonoperative treatment has failed.…”
Section: Introductionmentioning
confidence: 99%